Women Warriors and National Heroes A Global History - Cothran, Boyd; Judge, Joan; Shubert, Adrian (Bloomsbury Academic, 2019)
This volume presents women warriors and hero cults from a number of cultures since the early modern period. The first truly global study of women warriors, individual chapters examine figures such as Joan of Arc in Cairo, revenging daughters in Samurai Japan, a transgender Mexican revolutionary and WWII Chinese spies. Exploring issues of violence, gender fluidity, memory and nation-building, the authors discuss how these real or imagined female figures were constructed and deployed in different national and transnational contexts. Divided into four parts, they explore how women warriors and their stories were created, considers the issue of the violent woman, discusses how these female figures were gendered, and highlights the fate of women warriors who live on. It illustrates the ways in which female fighters have figured in nation-building stories and in the ordering or re-ordering of gender politics, and gives the history of women fighters a critical edge.